Are Household Production Decisions Cooperative? Evidence on Pastoral Migration and Milk Sales from Northern Kenya - Cheryl R. Doss; John G. McPeak (Yale University, Economic Growth Center, 2005)
Market-based development efforts frequently create opportunities to generate income from goods previously produced and consumed within the household. Production within the household is often characterized by a gender and age division of labor. Market development efforts to improve well being may lead to unanticipated outcomes if household production decisions are non-cooperative. We develop and test models of household decision-making to investigate intra-household decision making in a nomadic pastoral setting from Kenya. Our results suggest that household decisions are contested, with husbands using migration decisions to resist wives' ability to market milk.
Keywords: D13; O12; 330; Intrahousehold decision-making; household production; Kenya; Haushaltsproduktion; Entscheidung; Nomaden; Milchviehhaltung; Kenia